AUCTION AND DIRECT SALE OF CONFISCATED OBJECTS OR STATE LOOT BY THE DENPASAR DISTRICT ATTORNEY'S OFFICE - Juwita Arsawati, Ni Nyoman; Dewi, Dewa Ayu Susanti (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
A person who commits a crime generally uses an object or goods to make it easier for him to do something he wants, this item is what is commonly referred to as evidence. The Attorney General's Office is an independent institution that has the authority to prosecute and execute Judge decisions. If the judge decides to confiscate the evidence for the state, the Attorney General's Office has several methods or ways of managing the confiscated goods. From this report, the problems can be drawn, namely how the status flow of evidence or confiscated goods to be auctioned and sold directly confiscated by the Denpasar District Prosecutor's Office, what are the legal arrangements regarding auctions and direct sales of confiscated goods confiscated by the Denpasar District Prosecutor's Office, what is the process of auctioning and selling the confiscated goods immediately seized by the Denpasar District Attorney. The author suggests that the Attorney General's Office create a new internal administrative body that takes care of auction administrative activities starting from assessing the physical appearance and price of the loot to selling the loot at auction. The Prosecutor's Office has specific standards in managing confiscation as well as certain processes for evidence that have several legal sources.